Project management for information systems. - Cadle, James, ....-; Yeates, Donald, ....- (Harlow : Pearson, 2008)
Cadle and Yeates' Project Management for Information Systems is suitable for undergraduate students studying Project Management within the IT environment. This comprehensive and practical book is an excellent starting point for any students of Project Management for Information Systems, whether they are from a computing or a business background, at undergraduate or masters level. The authors strike a good balance - covering both the mechanics of project management and the human factors involved and include plenty of case studies and exercises as well as good and bad examples from real life. This fifth edition has new material on: development life-cycles and approaches (including agile approaches) different types of IS projects and how to manage them implementing change through information systems updated coverage of leadership and management.